2021
DOI: 10.3389/fevo.2021.583136
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Leucistic Texas Rat Snake Pantherophis obsoletus

Abstract: Albinism and leucism are phenotypes resulting from impaired melanin pigmentation in the skin and skin appendages. However, melanin pigmentation of eyes remains unaffected in leucism. Here, using transmission electron microscopy, we show that the leucistic morph of the Texas rat snake (Pantherophis obsoletus lindheimeri) lacks both melanophores and xanthophores in its skin and exhibits a uniform ivory white color generated by iridophores and collagen fibers. In addition, we sequenced the full genome of a leucis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 77 publications
(100 reference statements)
2
17
0
Order By: Relevance
“…Woodcock et al . 2017; Ullate-Agote and Tzika 2021), and the association between all-white skin and EDNRB1 in ball pythons is consistent with EDNRB1 controlling chromatophore development throughout vertebrates (reviewed in Braasch and Schartl 2014). We propose that all-white skin represents the null phenotype for EDNRB1 in ball pythons.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Woodcock et al . 2017; Ullate-Agote and Tzika 2021), and the association between all-white skin and EDNRB1 in ball pythons is consistent with EDNRB1 controlling chromatophore development throughout vertebrates (reviewed in Braasch and Schartl 2014). We propose that all-white skin represents the null phenotype for EDNRB1 in ball pythons.…”
Section: Discussionmentioning
confidence: 63%
“…Leucism is characteristic of an absence of chromatophores (e.g. Ullate-Agote and Tzika 2021), and the association between leucism and EDNRB1 in ball pythons is consistent with EDNRB1 controlling chromatophore development in zebrafish (Parichy et al . 2000) and mammals (Hosoda et al .…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…In addition to these transcriptomic studies, a recent genomic study on the European common wall-lizard ( Podarcis muralis , Lacertidae) identified a gene from the pteridine pathway [Sepiapterin Reductase ( SPR )] as responsible for determining whether an animal has orange or yellow spots ( Andrade et al 2019 ). Studies on wild squamate populations like these, however, have generally not discussed a role for color-pattern genes, with recent efforts in identifying the genetic basis of squamate color-pattern coming from studies on captive-bred snake color-mutants (e.g., Ullate-Agote and Tzika 2021 ). Our primary aim, therefore, was to use transcriptomic analyses to identify both candidate color and color-pattern genes in a wild polymorphic population of anole lizards from Hispaniola.…”
Section: Introductionmentioning
confidence: 99%